2017
DOI: 10.1007/s13246-017-0571-1
|View full text |Cite
|
Sign up to set email alerts
|

Fusion of heart rate variability and pulse rate variability for emotion recognition using lagged poincare plots

Abstract: Designing an efficient automatic emotion recognition system based on physiological signals has attracted great interests within the research of human-machine interactions. This study was aimed to classify emotional responses by means of a simple dynamic signal processing technique and fusion frameworks. The electrocardiogram and finger pulse activity of 35 participants were recorded during rest condition and when subjects were listening to music intended to stimulate certain emotions. Four emotion categories, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 39 publications
0
29
0
2
Order By: Relevance
“…It is possible to see that most selected studies used a sample with healthy subjects ( Holand et al, 1999 ; Martin-Soelch et al, 2006 ; Uclés et al, 2006 ; Koelsch et al, 2007 ; Kasprzak, 2010 ; Lee et al, 2010 ; Dousty et al, 2011 ; Sancini et al, 2012 ; Chen et al, 2014b ; Naji et al, 2014b ; Pérez-Lloret et al, 2014 ; da Silva and Backs, 2015 ; Krabs et al, 2015 ; Nardelli et al, 2015 ; Nozaki et al, 2015 ; Sim et al, 2015 ; Watanabe et al, 2015 ; Nakajima et al, 2016 ; El Aarbaoui et al, 2017 ; Goshvarpour et al, 2017 ; Ishimitsu et al, 2017 ). Samples are also used with a combination of males and females ( Martin-Soelch et al, 2006 ; Björ et al, 2007 ; Koelsch et al, 2007 ; Lee et al, 2010 ; Orini et al, 2010 ; Kraus et al, 2013 ; Naji et al, 2014b ; da Silva and Backs, 2015 ; Nozaki et al, 2015 ; Bidin et al, 2016 ; El Aarbaoui et al, 2017 ; Goshvarpour et al, 2017 ). There were few studies with just males ( Tomei et al, 2000 ; Cho et al, 2011 ; Gupta and Gupta, 2015 ; Walker et al, 2016 ) or just females ( Binns-Turner et al, 2011 ; Rhomberg et al, 2014 ; Nakajima et al, 2016 ; Abedi et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It is possible to see that most selected studies used a sample with healthy subjects ( Holand et al, 1999 ; Martin-Soelch et al, 2006 ; Uclés et al, 2006 ; Koelsch et al, 2007 ; Kasprzak, 2010 ; Lee et al, 2010 ; Dousty et al, 2011 ; Sancini et al, 2012 ; Chen et al, 2014b ; Naji et al, 2014b ; Pérez-Lloret et al, 2014 ; da Silva and Backs, 2015 ; Krabs et al, 2015 ; Nardelli et al, 2015 ; Nozaki et al, 2015 ; Sim et al, 2015 ; Watanabe et al, 2015 ; Nakajima et al, 2016 ; El Aarbaoui et al, 2017 ; Goshvarpour et al, 2017 ; Ishimitsu et al, 2017 ). Samples are also used with a combination of males and females ( Martin-Soelch et al, 2006 ; Björ et al, 2007 ; Koelsch et al, 2007 ; Lee et al, 2010 ; Orini et al, 2010 ; Kraus et al, 2013 ; Naji et al, 2014b ; da Silva and Backs, 2015 ; Nozaki et al, 2015 ; Bidin et al, 2016 ; El Aarbaoui et al, 2017 ; Goshvarpour et al, 2017 ). There were few studies with just males ( Tomei et al, 2000 ; Cho et al, 2011 ; Gupta and Gupta, 2015 ; Walker et al, 2016 ) or just females ( Binns-Turner et al, 2011 ; Rhomberg et al, 2014 ; Nakajima et al, 2016 ; Abedi et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…There were few studies with just males ( Tomei et al, 2000 ; Cho et al, 2011 ; Gupta and Gupta, 2015 ; Walker et al, 2016 ) or just females ( Binns-Turner et al, 2011 ; Rhomberg et al, 2014 ; Nakajima et al, 2016 ; Abedi et al, 2017 ). With respect to the sample size, many of the studies used a size between 20 and 33 ( Holand et al, 1999 ; Thayer and Faith, 2001 ; Chang et al, 2004 ; Martin-Soelch et al, 2006 ; Björ et al, 2007 ; Kasprzak, 2010 ; Krantz et al, 2010 ; Binns-Turner et al, 2011 ; Cho et al, 2011 ; Dousty et al, 2011 ; Croy et al, 2013 ; Naji et al, 2014b ; Pérez-Lloret et al, 2014 ; Nardelli et al, 2015 ; Nozaki et al, 2015 ; Al-Galal et al, 2016 ; Abedi et al, 2017 ) or 35 and 88 ( Tomei et al, 2000 ; Kenntner-Mabiala et al, 2007 ; Koelsch et al, 2007 ; Raggam et al, 2007 ; Graham et al, 2009 ; Orini et al, 2010 ; Sancini et al, 2012 ; Rhomberg et al, 2014 ; Gruhlke et al, 2015 ; Gupta and Gupta, 2015 ; Hajizadeh et al, 2015 ; Krabs et al, 2015 ; Sim et al, 2015 ; Watanabe et al, 2015 ; Gallasch et al, 2016 ; Goshvarpour et al, 2016a , 2017 ; El Aarbaoui et al, 2017 ) subjects. There were few studies with a sample larger than 100 subjects ( Thayer and Faith, 2001 ; Yuan et al, 2005 ; Uclés et al, 2006 ; Goyal et al, 2010 ; Kraus et al, 2013 ; Osiris et al, 2014 ; Tan et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Accuracy of the emotion recognition and classification based on physiological signals identification have improved significantly. Research by Goshvarpour et al using HRV and PRV, and fusion rules (feature level, decision level) showed classification rates improved up to 92% (sensitivity: 95%, specificity: 83.33%) [63]. Previous studies have provided evidence for general recognition rate from 57,77% to 85,46% for different emotional states, that more higher set of analyzed signals and more recognized emotions provides better results [64][65][66].…”
Section: Accuracymentioning
confidence: 98%